ANALISIS HEMOROID PADA IBU HAMIL DENGAN SISTEM CERTAINTY FACTOR - Indri Damayani; Sudarmin Sudarmin; Rizaldi Piliang (Jurnal Sistem Informasi dan Informatika (Simika), 2025)
Hemorrhoids in pregnant women are a physiological condition that often accompanies pregnancy. Women who had hemorrhoids before pregnancy are at a higher risk of developing them during pregnancy. The main concern is the possibility of bleeding, which may lead to anemia and negatively impact fetal development. To assist in analyzing the symptoms of hemorrhoids in pregnant women, an expert system was developed using the Certainty Factor method. This system aims to provide early detection and quick action recommendations for patients at Tanjungbalai General Hospital. The expert system is web-based and uses the Certainty Factor method to diagnose hemorrhoids based on symptoms entered by the user. The system calculates the confidence value of each possible disease and provides a diagnosis with a certainty percentage. Based on the CF calculation results, the highest CF value obtained is 0.7475 or 75%, indicating that the most likely diagnosis for the user’s symptoms is Internal Hemorrhoids (P01). The developed system includes features such as user registration, symptom consultation, and disease information. The administrator panel allows experts to manage disease data, symptom data, diagnostic rules, and user reports. Implemented using PHP and MySQL, this system helps pregnant women identify early symptoms of hemorrhoids, enabling timely treatment and reducing complications. By providing accurate diagnoses and suggested solutions, this expert system is expected to raise awareness and improve health outcomes for pregnant women suffering from hemorrhoids.